Kimchi : essential recipes of the Korean kitchen - Byung-Hi, Lim (Pavilion, 2014)
You can't really imagine Korea without kimchi. For thousands of years, their fermented vegetables have been absolutely essential at meals. In Korea, kimchi is so much more than food - it is a national cultural treasure, a universal health food and a part of the Korean identity.